You are on page 1of 20

# Class X Chapter 2 – Polynomials Maths

______________________________________________________________________________
Exercise 2.1

1.
Sol:
(i) f(x) = 𝑥𝑥 2 − 2𝑥𝑥 − 8
𝑓𝑓(𝑥𝑥) = 𝑥𝑥 2 − 2𝑥𝑥 − 8 = 𝑥𝑥 2 − 4𝑥𝑥 + 2𝑥𝑥 − 8
= 𝑥𝑥(𝑥𝑥 − 4) + 2(𝑥𝑥 − 4)
= (𝑥𝑥 + 2)(𝑥𝑥 − 4)
Zeroes of the polynomials are -2 and 4
− 𝑐𝑐𝑐𝑐 𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒 𝑜𝑜𝑜𝑜 𝑥𝑥
Sum of the zeroes = 𝑐𝑐𝑐𝑐 𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒 𝑜𝑜𝑜𝑜 𝑥𝑥
−(−2)
-2 + 4 =
1
2=2
𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐 𝑡𝑡𝑡𝑡𝑡𝑡𝑡𝑡
Product of the zeroes = 𝑐𝑐𝑐𝑐 𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒 𝑜𝑜𝑜𝑜 𝑥𝑥 2
−8
= 24 = 1
− 8 = −8
∴ Hence the relationship verified
(ii) 9(5) = 45 − 45 + 1 = 452 − 25 − 25 + 1 = 25(25 − 1) − 1(25 − 1)
= (25 − 1)(25 − 1)
1 1
Zeroes of the polynomials are 2 𝑎𝑎𝑎𝑎𝑎𝑎 2
− 𝑐𝑐𝑐𝑐 𝑒𝑒𝑒𝑒𝑒𝑒𝑖𝑖𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐 𝑜𝑜𝑜𝑜 𝑠𝑠
Sum of zeroes = 𝑐𝑐𝑐𝑐 𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒 𝑜𝑜𝑜𝑜 𝑠𝑠2
1 1 −(−4)
2
+2=
4
1=1
𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐 𝑡𝑡𝑡𝑡𝑡𝑡𝑡𝑡
Product of the zeroes = 𝑐𝑐𝑐𝑐 𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒 𝑜𝑜𝑜𝑜 𝑠𝑠2
1 1 1 1 1
2
×2=4⇒4=4
∴ Hence the relationship verified.
2
(iii) h(t) = 𝑡𝑡 2 − 15 = (𝑡𝑡 2 ) − �√15� = �𝑡𝑡 + √15��𝑡𝑡 − √15�
zeroes of the polynomials are −√15 𝑎𝑎𝑎𝑎𝑎𝑎 √15
sum of zeroes = 0
−√15 + √15 = 0
0=0
−15
Product of zeroes = 1
−√15 × √15 = −15
−15 = -15
∴ Hence the relationship verified.
(iv) p(x) = 𝑥𝑥 2 + 2√2𝑥𝑥 − 6 = 𝑥𝑥 2 + 3√2𝑥𝑥 + √2 × 3√2

Printed from Vedantu.com. Book a free session with a top LIVE online tutor now.
1

Class X Chapter 2 – Polynomials Maths
______________________________________________________________________________

= 𝑥𝑥�𝑥𝑥 + 3√2� − √2�2 + 3√2� = �𝑥𝑥 − √2��𝑥𝑥 + 3√2�
Zeroes of the polynomial are 3√2 and -3√2
−3√2
Sum of the zeroes = 1
√2 − 3√2 = −2√2
−2√2 = −2√2
6
𝑃𝑃𝑃𝑃𝑃𝑃𝑃𝑃𝑃𝑃𝑃𝑃𝑃𝑃 𝑜𝑜𝑜𝑜 𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧 ⇒ √2 × −3√2 = − 1
−6 = −6
𝐻𝐻𝐻𝐻𝐻𝐻𝐻𝐻𝐻𝐻 𝑡𝑡ℎ𝑒𝑒 𝑟𝑟𝑟𝑟𝑟𝑟𝑟𝑟𝑟𝑟𝑟𝑟𝑟𝑟𝑟𝑟ℎ𝑖𝑖𝑖𝑖 𝑣𝑣𝑣𝑣𝑣𝑣𝑣𝑣𝑣𝑣𝑣𝑣𝑣𝑣𝑣𝑣
(v) 2(x) = √3𝑥𝑥 2 + 10𝑥𝑥 + 7√3 = √3𝑥𝑥 2 + 7𝑥𝑥 + 3𝑥𝑥 + 7√3
= √3𝑥𝑥�𝑥𝑥 + √3� + 7�𝑥𝑥 + √3�
= �√3𝑥𝑥 + 7��𝑥𝑥 + √3�
−7
Zeroes of the polynomials are −√3,
√3
−10
Sum of zeroes =
√3
7 −10 −10 −10
⇒ −√3 − = ⇒ =
√3 √3 √3 √3
7√3 √3𝑥𝑥−7
Product of zeroes = ⇒ =7
3 √30
⇒7=7
Hence, relationship verified.
(vi) f(x) = 𝑥𝑥 2 − �√3 + 1�𝑥𝑥 + √3 = 𝑥𝑥 2 − √3𝑥𝑥 − 𝑥𝑥 + √3
= x (x − √3) – 1 (x - √3)
= (x – 1) (x − √3)
Zeroes of the polynomials are 1 and √3
−{𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐 𝑜𝑜𝑜𝑜 𝑥𝑥} −�−√3−1�
Sum of zeroes = =
𝑐𝑐𝑐𝑐 𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒 𝑜𝑜𝑜𝑜 𝑟𝑟 2 1
1 + √3 = √3 + 1
𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐 𝑡𝑡𝑡𝑡𝑡𝑡𝑡𝑡 √3
Product of zeroes = 𝑐𝑐𝑐𝑐 𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒 𝑜𝑜𝑜𝑜 𝑥𝑥 2 = 1
1 × √3 = √3 = √3 = √3
∴ Hence, relationship verified
(vii) g(x) = 𝑎𝑎[(𝑥𝑥 2 + 1) − 𝑥𝑥(𝑎𝑎2 + 1)]2 = 𝑎𝑎𝑥𝑥 2 + 𝑎𝑎 − 𝑎𝑎2 𝑥𝑥 − 𝑥𝑥
= 𝑎𝑎𝑥𝑥 2 − [(𝑎𝑎2 + 1) − 𝑥𝑥] + 0 = 𝑎𝑎𝑥𝑥 2 − 𝑎𝑎2 𝑥𝑥 − 𝑥𝑥 + 𝑎𝑎
= 𝑎𝑎𝑎𝑎(𝑥𝑥 − 𝑎𝑎) − 1(𝑥𝑥 − 𝑎𝑎) = (𝑥𝑥 − 𝑎𝑎)(𝑎𝑎𝑎𝑎 − 1)
1
Zeroes of the polynomials = 𝑎𝑎 𝑎𝑎𝑎𝑎𝑎𝑎 𝑎𝑎
−�−𝑎𝑎2 −1�
Sum of the zeroes = 𝑎𝑎
1 𝑎𝑎2 +1 𝑎𝑎2 +1 𝑎𝑎2 +1
⇒ 𝑎𝑎 + 𝑎𝑎 = 𝑎𝑎
⇒ 𝑎𝑎
= 𝑎𝑎

Printed from Vedantu.com. Book a free session with a top LIVE online tutor now.
2

3 . Sol: f(x) = 𝑎𝑎𝑥𝑥 2 + 𝑏𝑏𝑏𝑏 + 𝑐𝑐 −𝑏𝑏 𝛼𝛼 + 𝛽𝛽 = 𝒂𝒂 𝑐𝑐 𝛼𝛼𝛼𝛼 = 𝑎𝑎 𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠 𝛼𝛼 + 𝛽𝛽 𝑎𝑎𝑎𝑎𝑎𝑎 𝑡𝑡ℎ𝑒𝑒 𝑟𝑟𝑟𝑟𝑟𝑟𝑟𝑟𝑟𝑟 (𝑜𝑜𝑜𝑜)𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧 𝑜𝑜𝑜𝑜 𝑡𝑡ℎ𝑒𝑒 𝑔𝑔𝑔𝑔𝑔𝑔𝑔𝑔𝑔𝑔 𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝 (i) 𝛼𝛼 − 𝛽𝛽 The two zeroes of the polynomials are −𝑏𝑏+√𝑏𝑏2 −4𝑎𝑎𝑎𝑎 −√𝑏𝑏2 −4𝑎𝑎𝑎𝑎 √𝑏𝑏 2 −4𝑎𝑎𝑎𝑎 +𝑏𝑏+√𝑏𝑏2 −4𝑎𝑎𝑎𝑎 2√𝑏𝑏 2 −4𝑎𝑎𝑎𝑎 √𝑏𝑏 2 −4𝑎𝑎𝑎𝑎 − �𝑏𝑏 � = −𝑏𝑏 + = = 2𝑎𝑎 2𝑎𝑎 2𝑎𝑎 2𝑎𝑎 2𝑎𝑎 1 1 𝛽𝛽−𝛼𝛼 −(𝛼𝛼− 𝛽𝛽) (ii) 𝛼𝛼 − 𝛽𝛽 = 𝛼𝛼𝛼𝛼 = … (𝑖𝑖) 𝛼𝛼𝛼𝛼 √𝑏𝑏 2 −4𝑎𝑎𝑎𝑎 𝑐𝑐 From (i) we know that 𝛼𝛼 − 𝛽𝛽 = [𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓 (𝑖𝑖)]𝛼𝛼𝛼𝛼 = 2𝑎𝑎 𝑎𝑎 √𝑏𝑏 2 −4𝑎𝑎𝑎𝑎×𝑎𝑎 −√𝑏𝑏 2 −4𝑎𝑎𝑎𝑎 Putting the values in the (a) = − � �= 𝑎𝑎×𝑐𝑐 𝑐𝑐 1 1 (iii) 𝛼𝛼 + 𝛽𝛽 − 2𝛼𝛼 𝛽𝛽 𝛼𝛼+ 𝛽𝛽 ⇒� 𝛼𝛼𝛼𝛼 � − 2𝛼𝛼𝛼𝛼 −𝑏𝑏 𝑎𝑎 𝑐𝑐 𝑐𝑐 𝑏𝑏 −𝑎𝑎𝑎𝑎−2𝑐𝑐 2 𝑏𝑏 2𝑐𝑐 ⇒ 𝑎𝑎 × 𝑐𝑐 − 2 𝑎𝑎 = −2 𝑎𝑎 − 𝑐𝑐 = − � 𝑐𝑐 + � 𝑎𝑎𝑎𝑎 𝑎𝑎 (iv) 𝛼𝛼 2 𝛽𝛽 + 𝛼𝛼 𝛽𝛽 2 𝛼𝛼 𝛽𝛽(𝛼𝛼 + 𝛽𝛽) 𝑐𝑐 −𝑏𝑏 = 𝑎𝑎 � 𝑎𝑎 � −𝑏𝑏𝑏𝑏 = 𝑎𝑎2 (v) 𝛼𝛼 + 𝛽𝛽 4 = (𝛼𝛼 2 + 𝛽𝛽 2 )2 − 2𝛼𝛼 2 + 𝛽𝛽 2 4 = ((𝛼𝛼 + 𝛽𝛽)2 − 2𝛼𝛼𝛼𝛼)2 − 2(𝛼𝛼𝛼𝛼)2 Printed from Vedantu.com. 2.Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ 𝑎𝑎 Product of zeroes = 𝑎𝑎 1 𝑎𝑎 𝑎𝑎2 +1 𝑎𝑎2 +1 ⇒ 𝑎𝑎 × 𝑎𝑎 = 𝑎𝑎 ⇒ 𝑎𝑎 = 𝑎𝑎 𝑎𝑎 Product of zeroes = 𝑎𝑎 ⇒ 1 = 1 Hence relationship verified (viii) 6𝑥𝑥 2 − 3 − 7𝑥𝑥 = 6𝑥𝑥 2 − 7𝑥𝑥 − 3 = (3𝑥𝑥 + 11)(2𝑥𝑥 − 3) 3 −1 Zeroes of polynomials are +2 𝑎𝑎𝑎𝑎𝑎𝑎 3 −1 3 7 −(−7) −(𝑐𝑐𝑐𝑐 𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒 𝑜𝑜𝑜𝑜 𝑥𝑥) Sum of zeroes = +2=6= = 3 6 𝑐𝑐𝑐𝑐 𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒 𝑜𝑜𝑜𝑜 𝑥𝑥 2 −1 3 −1 −3 𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐𝑐 𝑡𝑡𝑡𝑡𝑡𝑡𝑡𝑡 Product of zeroes = 3 ×2= 2 = 6 = 𝑐𝑐𝑐𝑐 𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒 𝑜𝑜𝑜𝑜 𝑥𝑥 2 ∴ Hence. relationship verified. Book a free session with a top LIVE online tutor now.

Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ 2 𝑏𝑏 2 𝑐𝑐 𝑐𝑐 2 = ��− 𝑎𝑎� − 2 𝑎𝑎� − �2 �𝑎𝑎� � 2 𝑏𝑏 2 −2𝑎𝑎𝑎𝑎 2𝑐𝑐 2 =� 𝑎𝑎2 � − 𝑎𝑎2 2 �𝑏𝑏 2 2𝑎𝑎𝑎𝑎� −2𝑎𝑎2 𝑐𝑐 2 = 𝑎𝑎4 1 1 (vi) 𝑎𝑎𝑎𝑎+𝑏𝑏 + 𝛼𝛼𝛼𝛼+𝑏𝑏 𝑎𝑎𝑎𝑎+𝑏𝑏+𝑎𝑎𝑎𝑎+𝑏𝑏 ⇒ (3𝛼𝛼+𝑏𝑏)(𝛼𝛼𝛼𝛼+𝑏𝑏) 𝑎𝑎(𝛼𝛼+ 𝛽𝛽)+2𝑏𝑏 = 𝑎𝑎2 𝛼𝛼𝛼𝛼+𝑎𝑎𝑎𝑎 𝛼𝛼+𝑎𝑎𝑎𝑎𝑎𝑎+𝑏𝑏2 𝑎𝑎(𝛼𝛼+𝛽𝛽)+𝑏𝑏 = 𝑎𝑎2 𝛼𝛼𝛼𝛼+𝛼𝛼𝛼𝛼(𝛼𝛼2 𝛽𝛽)+𝑏𝑏2 𝑎𝑎+2𝑏𝑏 𝑎𝑎× 𝑏𝑏 𝑏𝑏 = 𝑎𝑎 𝑐𝑐 𝑎𝑎𝑎𝑎𝑎𝑎(−𝑏𝑏)+𝑏𝑏2 = 𝑎𝑎𝑎𝑎−𝑏𝑏2 +𝑏𝑏2 = 𝑎𝑎𝑎𝑎 𝑎𝑎× + 𝑎𝑎 𝑎𝑎 𝛽𝛽 𝛼𝛼 (vii) 𝑎𝑎𝑎𝑎+𝑏𝑏 + 𝑎𝑎𝑎𝑎+𝑏𝑏 𝛽𝛽(𝑎𝑎𝑎𝑎+𝑏𝑏)+𝛼𝛼(𝑎𝑎𝑎𝑎+𝑏𝑏) = (𝑎𝑎𝑎𝑎+𝑏𝑏)(𝛼𝛼𝛼𝛼+𝑏𝑏) 𝑎𝑎𝛽𝛽 2 +𝑏𝑏𝑏𝑏+𝑎𝑎𝛼𝛼2 +𝑏𝑏𝑏𝑏 = 𝑎𝑎2 𝛼𝛼𝛼𝛼+𝑎𝑎𝑎𝑎𝑎𝑎+𝑎𝑎𝑎𝑎𝑎𝑎+𝑏𝑏2 𝑎𝑎𝛼𝛼2 +𝑎𝑎𝛽𝛽 2 +𝑏𝑏𝛽𝛽 2 +𝑏𝑏𝑏𝑏 = 𝑐𝑐 𝑎𝑎× +𝑎𝑎𝑎𝑎(𝛼𝛼+𝛽𝛽)+𝑏𝑏 2 𝑎𝑎 𝑎𝑎��𝛼𝛼2 +𝛽𝛽 2 �+𝑏𝑏(𝛼𝛼+𝛽𝛽)� = −𝑏𝑏 𝑎𝑎𝑎𝑎+𝑎𝑎𝑎𝑎+𝑥𝑥� �+𝑏𝑏2 𝑎𝑎 𝑏𝑏 𝑎𝑎�(𝛼𝛼+ 𝛽𝛽)2 −2𝛼𝛼𝛼𝛼�+𝑏𝑏𝑏𝑏− = 𝑎𝑎 𝑎𝑎𝑎𝑎 𝑏𝑏2 2𝑐𝑐 𝑏𝑏2 𝑏𝑏2 −2𝑐𝑐 𝑎𝑎� − �− 𝑎𝑎×� �−𝑏𝑏2 −2 𝑎𝑎 𝑎𝑎 𝑎𝑎 𝑎𝑎 = = = 𝑎𝑎𝑎𝑎 𝑎𝑎𝑎𝑎 𝑎𝑎 𝛼𝛼2 𝛽𝛽 2 𝛼𝛼 𝛽𝛽 (viii) 𝑎𝑎 � 𝛽𝛽 + � + 𝑏𝑏 �𝑎𝑎 + 𝛼𝛼� 𝛼𝛼 𝛼𝛼3 +𝛽𝛽 3 𝛼𝛼2 +𝛽𝛽 2 = 𝑎𝑎 � � + 𝑏𝑏 � � 𝛼𝛼𝛼𝛼 𝛼𝛼𝛼𝛼 𝛼𝛼�(𝛼𝛼+𝛽𝛽)3 −3𝛼𝛼𝛼𝛼 (𝛼𝛼+𝛽𝛽)� = 𝛼𝛼 𝛽𝛽 + 𝑏𝑏(𝛼𝛼 + 𝛽𝛽)2 − 2𝛼𝛼 𝛽𝛽 −𝑏𝑏3 3𝑏𝑏 𝑐𝑐 𝑏𝑏2 2𝑐𝑐 𝛼𝛼�� 3 �+ . 4 . +𝑏𝑏� 2 − �� 𝑎𝑎 𝑎𝑎 𝑎𝑎 𝑎𝑎 𝑎𝑎 = 𝑐𝑐 𝑎𝑎 𝑎𝑎2 −𝑏𝑏3 3𝑏𝑏𝑏𝑏 𝑏𝑏 3 2𝑏𝑏𝑏𝑏 = � 𝑎𝑎3 + 𝑎𝑎2 + 𝑎𝑎2 − � 𝑐𝑐 𝑎𝑎 −𝑎𝑎2 𝑏𝑏 3 3𝑎𝑎2 𝑏𝑏𝑏𝑏 𝑏𝑏 3 𝑎𝑎2 2𝑏𝑏𝑏𝑏𝑎𝑎2 = + + − 𝑐𝑐𝑎𝑎3 𝑐𝑐𝑎𝑎2 𝑎𝑎2 𝑐𝑐 𝑎𝑎𝑎𝑎 −𝑏𝑏 3 𝑏𝑏 3 = + 3𝑏𝑏 + 𝑎𝑎𝑎𝑎 − 2𝑏𝑏 𝑎𝑎𝑎𝑎 =b Printed from Vedantu.com. Book a free session with a top LIVE online tutor now.

Sol: Since 𝛼𝛼 𝑎𝑎𝑎𝑎𝑎𝑎 𝛽𝛽 are the roots of the polynomial: 4𝑥𝑥 2 − 5𝑥𝑥 − 1 5 ∴ Sum of the roots 𝛼𝛼 + 𝛽𝛽 = 4 −1 Product of the roots 𝛼𝛼𝛼𝛼 = 4 2 2 5 −1 −5 Hence 𝛼𝛼 𝛽𝛽 + 𝛼𝛼𝛽𝛽 = 𝛼𝛼𝛼𝛼(𝛼𝛼 + 𝛽𝛽) = 4 � 4 � = 16 6. Sol: Since 𝛼𝛼 and 𝛽𝛽 are the roots of the polynomial x + x – 2 ∴ Sum of roots 𝛼𝛼 + 𝛽𝛽 = 1 1 Product of roots 𝛼𝛼𝛼𝛼 2 ⇒ − 𝛽𝛽 𝛽𝛽−𝛼𝛼 (𝛼𝛼−𝛽𝛽) = 𝛼𝛼𝛼𝛼 ∙ 𝛼𝛼𝛼𝛼 �(𝛼𝛼+𝛽𝛽)2 −4𝛼𝛼𝛼𝛼 = 𝛼𝛼𝛼𝛼 Printed from Vedantu. Sol: Since 𝛼𝛼 + 𝛽𝛽 are the zeroes of the polynomial: 𝑥𝑥 2 − 𝑥𝑥 − 4 Sum of the roots (𝛼𝛼 + 𝛽𝛽) = 1 Product of the roots (𝛼𝛼𝛼𝛼) = −4 1 1 𝛼𝛼+𝛽𝛽 𝛼𝛼 + 𝛽𝛽 − 𝛼𝛼𝛼𝛼 = 𝛼𝛼𝛼𝛼 − 𝛼𝛼𝛼𝛼 1 −1 −1+16 15 = −4 + 4 = 4 +4 = 4 = 4 5. Sol: f(x) = 6𝑥𝑥 2 − 𝑥𝑥 − 2 Since 𝛼𝛼 and 𝛽𝛽 are the zeroes of the given polynomial −1 ∴ Sum of zeroes [𝛼𝛼 + 𝛽𝛽] = 6 −1 Product of zeroes (𝛼𝛼𝛼𝛼) = 3 𝛼𝛼 𝛽𝛽 𝛼𝛼2 +𝛽𝛽 2 (𝛼𝛼+ 𝛽𝛽)2 −2𝛼𝛼𝛼𝛼 = 𝛽𝛽 + 𝛼𝛼 = = 𝛼𝛼𝛼𝛼 𝛼𝛼𝛼𝛼 1 2 −1 1 2 1+24 � � −2×� � − 6 3 = 1 = 6 3 −1 = 36 −1 − 3 3 3 2 −25 = 36 1 = 12 3 4. 5 . Book a free session with a top LIVE online tutor now.com.Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ 3.

Sol: Since 𝛼𝛼 𝑎𝑎𝑎𝑎𝑎𝑎 𝛽𝛽 are the zeroes of the polynomial f(t) = 𝑡𝑡 2 − 4𝑡𝑡 + 3 Since α + β = 4 Product of zeroes 𝛼𝛼𝛼𝛼 = 3 𝐻𝐻𝐻𝐻𝐻𝐻𝐻𝐻𝐻𝐻 𝛼𝛼 4 𝛽𝛽 3 + 𝛼𝛼 3 𝛽𝛽 4 = 𝛼𝛼 3 𝛽𝛽 3 (𝛼𝛼 + 𝛽𝛽) = [3]3 [4] = 108 9. Sol: Since 𝛼𝛼 𝑎𝑎𝑎𝑎𝑎𝑎 𝛽𝛽 are the zeroes of the polynomials 6 Sum of the zeroes 𝛼𝛼 + 𝛽𝛽 = 3 4 Product of the zeroes 𝛼𝛼𝛼𝛼 = 3 𝛼𝛼 𝛽𝛽 1 1 𝛽𝛽 + 𝛼𝛼 + 2 �𝛼𝛼 + 𝛽𝛽� + 3𝛼𝛼𝛼𝛼 𝛼𝛼2 +𝛽𝛽 2 𝛼𝛼+𝛽𝛽 ⇒ + 2� � + 3𝛼𝛼𝛼𝛼 𝛼𝛼𝛼𝛼 𝛼𝛼𝛼𝛼 (𝛼𝛼+𝛽𝛽)2 −2𝛼𝛼𝛼𝛼 𝛼𝛼+𝛽𝛽 ⇒ 𝛼𝛼𝛼𝛼 + 2 � 𝛼𝛼𝛼𝛼 � + 3𝛼𝛼𝛼𝛼 Printed from Vedantu. Sol: Since 𝛼𝛼 𝑎𝑎𝑎𝑎𝑎𝑎 𝛽𝛽 are the roots of the quadratic polynomial f(x) = 𝑥𝑥 2 − 5𝑥𝑥 + 4 Sum of roots = 𝛼𝛼 + 𝛽𝛽 = 5 Product of roots = 𝛼𝛼𝛼𝛼 = 4 1 1 𝛽𝛽+𝛼𝛼 5 5 −27 𝛼𝛼 + 𝛽𝛽 − 2𝛼𝛼𝛼𝛼 = 𝛼𝛼𝛼𝛼 − 2𝛼𝛼𝛼𝛼 = 4 − 2 × 4 = 4 − 8 = 4 8. Book a free session with a top LIVE online tutor now. 6 .com. Sol: Since 𝛼𝛼 𝑎𝑎𝑎𝑎𝑎𝑎 𝛽𝛽 are the zeroes of the polynomials p(y) = 542 = 5y2 – 7y + 1 1 Sum of the zeroes 𝛼𝛼 𝛽𝛽 = 6 1 Product of zeroes = 𝛼𝛼 𝛽𝛽 = 6 1 1 𝛼𝛼+𝛽𝛽 7×5 𝛼𝛼 + 𝛽𝛽 = 𝛼𝛼𝛼𝛼 = 5×1 = 7 10.Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ √1+8 3 = =2 +2 7.

Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ 4 2×3 4 [2]2 −2× +2� �+3� � 3 4 3 = 4 3 8 4− 4 3 = 4 3 + 7 ⇒ 3 × 4 (1 + 7) ⇒ 8 3 11. Sol: Since 𝛼𝛼 and 𝛽𝛽 are the roots of the polynomials f(x) = 𝑥𝑥 2 − 𝑝𝑝𝑝𝑝 + 2 sum of zeroes = p = 𝛼𝛼 + 𝛽𝛽 Product of zeroes = q = 𝛼𝛼𝛼𝛼 α2 𝛽𝛽 2 LHS = 𝛽𝛽2 + 𝛼𝛼2 2 𝛼𝛼2 +𝛽𝛽 2 �α2 + β2 � −2(𝛼𝛼𝛼𝛼)2 = = 𝛼𝛼𝛽𝛽 2 (𝛼𝛼𝛼𝛼)2 2 �(𝛼𝛼+𝛽𝛽)2 −2𝛼𝛼𝛼𝛼� −2(𝛼𝛼𝛼𝛼)2 = (𝛼𝛼𝛼𝛼)2 2 �(𝑝𝑝)2 −2𝑞𝑞� −2𝑞𝑞 2 = 𝑞𝑞 𝑝𝑝4 +4𝑞𝑞 2 −2𝑝𝑝2 .com. 7 .2𝑞𝑞−2𝑞𝑞 2 = 𝑞𝑞 2 𝑝𝑝4 +2𝑞𝑞 2 −4𝑝𝑝2 𝑞𝑞 𝑝𝑝4 4𝑝𝑝2 = 𝑞𝑞 2 = 𝑞𝑞2 + 2 − 𝑞𝑞 𝑝𝑝4 4𝑝𝑝2 𝑝𝑝4 4𝑝𝑝2 = 𝑞𝑞2 − = 𝑞𝑞2 + 2 − 𝑞𝑞 2 𝑞𝑞 𝑝𝑝4 4𝑝𝑝2 = 𝑞𝑞2 − +2 𝑞𝑞 12. Sol: Let the two zeroes of the polynomial be 𝛼𝛼 and 𝛽𝛽 f(x) = 𝑥𝑥 2 + 𝑝𝑝𝑝𝑝 + 45 sum of the zeroes = −𝑝𝑝 Product of zeroes = 45 ⇒ (α − β)2 − 4αβ = 144 ⇒ 𝑝𝑝2 − 4 × 45 = 144 ⇒ 𝑝𝑝2 = 144 + 180 ⇒ 𝑝𝑝2 = 324 𝑝𝑝 = ±1 Printed from Vedantu. Book a free session with a top LIVE online tutor now.

com.Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ 13. Sol: Let the two zeroes of the f(t) = 𝑘𝑘𝑡𝑡 2 + 2𝑡𝑡 + 3𝑘𝑘 𝑏𝑏𝑏𝑏 α and β Sum of the zeroes (α + β) Product of the zeroes αβ −2 3𝑘𝑘 k = k −2𝑘𝑘 = 3𝑘𝑘 2 2𝑘𝑘 + 3𝑘𝑘 2 = 0 k(3k + 2) = 0 k=0 −2 k= 3 14. Sol: f(x) = 𝑥𝑥 2 − 1 sum of zeroes 𝛼𝛼 + 𝛽𝛽 = 0 Product of zeroes α𝛽𝛽 = -1 2α 2𝛽𝛽 2α2 +2𝛽𝛽2 Sum of zeroes = 𝛽𝛽 + α = α𝛽𝛽 2�(α+𝛽𝛽)2 −2α𝛽𝛽� = α𝛽𝛽 2�(0)2 −2× −1� = −1 2(2)1 = −1 = −4 2α×2𝛽𝛽 4α𝛽𝛽 Product of zeroes = α𝛽𝛽 = α𝛽𝛽 Hence the quadratic equation is 𝑥𝑥 2 − (𝑠𝑠𝑠𝑠𝑠𝑠 𝑜𝑜𝑜𝑜 𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧)𝑥𝑥 + 𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝 𝑜𝑜𝑜𝑜 𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧 Printed from Vedantu. 8 . −α −9 α×α = 4 2 +9 tα = 4 +3 𝛼𝛼 = 2 8𝑘𝑘 Sum of zeroes = 4 =0 Hence 8k = 0 Or k = 0 15. Sol: Let the two zeroes of one polynomial 𝑓𝑓(𝑥𝑥) = 4𝑥𝑥 2 − 5𝑘𝑘 − 9 𝑏𝑏𝑏𝑏 α. Book a free session with a top LIVE online tutor now.

Book a free session with a top LIVE online tutor now.Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ = 𝑘𝑘(𝑥𝑥 2 + 4𝑥𝑥 + 14) 16. 2 𝛼𝛼 =32 𝛼𝛼 = 16 𝛽𝛽 = 8 𝛼𝛼 𝛽𝛽 = 16 × 8 = 128 Quadratic equation ⇒ 𝑥𝑥 2 − (𝑠𝑠𝑠𝑠𝑠𝑠 𝑜𝑜𝑜𝑜 𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧) + 𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝 𝑜𝑜𝑜𝑜 𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧 ⇒ 𝑘𝑘[𝑥𝑥 2 − 24𝑥𝑥 + 128] Printed from Vedantu. 9 . Sol: 𝛼𝛼 + 𝛽𝛽 = 24 𝛼𝛼 𝛽𝛽 = 8 ………….com. Sol: 𝑓𝑓(𝑥𝑥) = 𝑥𝑥 2 − 3𝑥𝑥 − 2 Sum of zeroes [α + 𝛽𝛽] = 3 Product of zeroes [α𝛽𝛽] = -2 1 1 Sum of zeroes = 2α+𝛽𝛽 + 2𝛽𝛽+α 2𝛽𝛽+α+2α+𝐴𝐴 = (2α+𝛽𝛽)(2𝛽𝛽+α) 3α+3𝛽𝛽 = 2(α2 +𝛽𝛽2 )+5α𝛽𝛽 3 ×3 = 2[2 (α+𝛽𝛽)2 −2α𝛽𝛽 +5×(−2)] 9 9 = 2[9]−10 = 16 1 1 1 Product of zeroes = α+𝛽𝛽 × 2𝛽𝛽+α = 4α𝛽𝛽+α𝛽𝛽+2α2 +2𝛽𝛽2 1 = 5×−2+2[(α+𝛽𝛽)2 −2α𝛽𝛽] 1 = −10+2[9+4] 1 = 10+26 1 = 16 Quadratic equation = 𝑥𝑥 2 − [𝑠𝑠𝑠𝑠𝑠𝑠 𝑜𝑜𝑜𝑜 𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧]𝑥𝑥 + 𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝𝑝 𝑜𝑜𝑜𝑜 𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧 9𝑥𝑥 1 = 𝑥𝑥 2 − 16 + 16 9𝑥𝑥 1 = 𝑘𝑘 �𝑥𝑥 2 − 16 + 16� 17.

Sol: 𝑓𝑓(𝑥𝑥) = 𝑥𝑥 2 − 𝑝𝑝(𝑥𝑥 + 1)𝑐𝑐 = 𝑥𝑥 − 𝑝𝑝𝑝𝑝 = −𝑝𝑝 − 𝑐𝑐 Sum of zeroes = 𝛼𝛼 + 𝛽𝛽 = p Product of zeroes = − p – c = 𝛼𝛼 𝛽𝛽 (𝛼𝛼 + 1+ 𝛽𝛽+ ) = 𝛼𝛼 𝛽𝛽+ 𝛼𝛼 + 𝛽𝛽 + 1 = −p –c + p + 1 = 1 – c = R.Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ 18.S ∴ Hence proved 19. 10 . Sol: 𝑓𝑓(𝑥𝑥) = 𝑥𝑥 2 − 2𝑥𝑥 + 3 Sum of zeroes = 2 = (𝛼𝛼 + 𝛽𝛽) Product of zeroes = 3 = (𝛼𝛼 𝛽𝛽) (𝑖𝑖) 𝑠𝑠𝑠𝑠𝑠𝑠 𝑜𝑜𝑜𝑜 𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧 = (α + 2) + (β + 2) = α + β + 4 = 2 + 4 = 6 𝑃𝑃𝑃𝑃𝑃𝑃𝑃𝑃𝑃𝑃𝑃𝑃𝑃𝑃 𝑜𝑜𝑜𝑜 𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧 = (α + 2)(β + 2) = α β + 2α + 2β + 4 = 3 + 2(2) + 4 = 11 𝑄𝑄𝑄𝑄𝑄𝑄𝑄𝑄𝑄𝑄𝑄𝑄𝑄𝑄𝑄𝑄𝑄𝑄 𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒𝑒 = 𝑥𝑥 2 − 6𝑥𝑥 + 11 = 𝑘𝑘[𝑥𝑥 2 − 6𝑥𝑥 + 11] α−1 β−1 (ii) sum of zeroes = α+1 + β+1 (α−1)(β+1)+(β−1)(α+1) = (α+1)(β+1) α β+α−β−1+α β+β+β−α−1 = 3+2+1 3−1+3−1 2 = 3+2+1 =4=3 α−1 β−1 α 1−α−αβ+1 Product of zeroes = βα +1 × α+1 − α β+α+β+1 3−(α+β)+1 2 1 = 3+2+1 =6=3 2 +1 𝑥𝑥 2 −2𝑥𝑥 1 Quadratic equation on 𝑥𝑥 2 − 3 × 3 = 1� 3 + 3� 20.com. Book a free session with a top LIVE online tutor now. Sol: 𝑓𝑓(𝑥𝑥) = 𝑥𝑥 2 + 𝑝𝑝 + 𝑞𝑞 Sum of zeroes = p = 𝛼𝛼 + 𝛽𝛽 Product of zeroes = q = 𝛼𝛼 𝛽𝛽 Sum of the new polynomial = (α + β)2 + (α − β)2 = (−𝑝𝑝)2 + α2 + β2 − 2α β = 𝑝𝑝2 + (α + β)2 − 2α β − 2α β = 𝑝𝑝2 + 𝑝𝑝2 − 4𝑞𝑞 = 2𝑝𝑝2 − 4𝑞𝑞 Printed from Vedantu.H.

Book a free session with a top LIVE online tutor now.2 1. 11 . 𝛽𝛽𝛽𝛽 + 𝑟𝑟𝑟𝑟 = 𝑎𝑎 1 1 −5 2 × 1 + 1 × −2 + −2 × 2 = 2 1 −5 2 −2−1= 2 −5 −5 2 = 2 (𝑖𝑖𝑖𝑖) 𝑔𝑔(𝑥𝑥) = 𝑥𝑥 3 − 4𝑥𝑥 2 + 5 × −2 𝑔𝑔(2) = (2)3 − 4(2)2 + 5(2) − 2 = 8 − 16 + 10 − 2 = 18 − 18 = 0 𝑔𝑔(1) = [1]3 − 4[1]2 + 5[1] − 2 = 1 − 4 + 5 − 2 = 6 − 6 = 0 −𝑏𝑏 𝛼𝛼 + 𝛽𝛽 + 𝛾𝛾 = (2) + 1 + 1 = −(−4) = 4 = 4 𝑎𝑎 𝑐𝑐 𝛼𝛼 𝛽𝛽 + 𝛽𝛽 𝛾𝛾 + 𝛾𝛾𝛾𝛾 = 𝑎𝑎 2 × 1 + 1 𝛼𝛼 1 + 1 × 2 = 5 2+1+2=5 Printed from Vedantu.com.Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ Product of zeroes = (α + β)2 × (α − β)2 = [−𝑝𝑝]2 × (𝑝𝑝2 − 4𝑞𝑞) = (𝑝𝑝2 − 4𝑞𝑞)𝑝𝑝2 Quadratic equation = 𝑥𝑥 2 − [2𝑝𝑝2 − 4𝑞𝑞] + 𝑝𝑝2 [−4𝑞𝑞 + 𝑝𝑝] 𝑓𝑓(𝑥𝑥) = 𝑘𝑘{𝑥𝑥 2 − 2(𝑝𝑝2 − 28)𝑥𝑥 + 𝑝𝑝2 (𝑞𝑞 2 − 4𝑞𝑞)} Exercise 2. Sol: (𝑖𝑖) 𝑓𝑓(𝑥𝑥) = 2𝑥𝑥 3 + 𝑥𝑥 2 − 5𝑥𝑥 + 2 1 1 3 1 2 1 𝑓𝑓 �2� = 2 �2� + �2� − 5 �2� + 2 2 1 5 −4 =8+4−2+2= 2 +2=0 3 (1)2 𝑓𝑓(1) = 2(1) + − 5(1) + 2 = 2 + 1 − 5 + 2 = 0 𝑓𝑓(−2) = 𝑞𝑞(−2) + (−2)2 − 5(−2) + 2 3 = −16 + 4 + 10 + 2 = −16 + 16 = 0 −𝑏𝑏 = ∝ +𝛽𝛽 + 𝛾𝛾 = 𝑎𝑎 1 −1 2 +1−2= 2 1 −1 2 −1= 2 1 −1 2 = 2 𝑐𝑐 𝛼𝛼𝛼𝛼.

𝑎𝑎 + 𝑑𝑑 be the zeroes of the polynomial −𝑏𝑏 𝑇𝑇ℎ𝑒𝑒 𝑠𝑠𝑠𝑠𝑠𝑠 𝑜𝑜𝑜𝑜 𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧 = 𝑎𝑎 Printed from Vedantu. Sol: Let 𝛼𝛼 = a – d . Sol: 𝑓𝑓(𝑥𝑥) = 𝑥𝑥 3 + 3𝑝𝑝𝑥𝑥 2 + 3𝑞𝑞𝑞𝑞 + 𝑞𝑞 𝐿𝐿𝐿𝐿𝐿𝐿 𝑎𝑎 − 𝑑𝑑. 𝑓𝑓(𝑥𝑥) = 2𝑥𝑥 3 − 15𝑥𝑥 2 + 37𝑥𝑥 − 30 −15 15 𝛼𝛼 + 𝛽𝛽 + 𝛾𝛾 = − � 2 �= 2 −30 𝛼𝛼𝛼𝛼𝛼𝛼 = − � 2 � = 15 15 a–d+a+a+d= 2 and 𝑎𝑎(𝑎𝑎 − 𝑑𝑑)(𝑎𝑎 + 𝑎𝑎) = 15 15 5 3a = 2 .product of zeroes = 𝑥𝑥 3 − 2𝑥𝑥 2 + (3 − 𝑥𝑥) + 3 = k [𝑥𝑥 3 − 3𝑥𝑥 2 − 𝑥𝑥 − 3] k is any non-zero real numbers 3. 12 . 𝛽𝛽 = a and 𝛾𝛾 = a + d be the zeroes of polynomial. 𝑎𝑎. Book a free session with a top LIVE online tutor now.a=2 𝑎𝑎(𝑎𝑎2 − 𝑑𝑑2 ) = 15 15×2 5 2 25−6 𝑎𝑎2 − 𝑎𝑎2 = 5 ⇒ �2� − 𝑑𝑑2 = 6 ⇒⇒ 4 = 𝑑𝑑2 1 1 𝑑𝑑 2 = 4 ⇒ 𝑑𝑑 = 2 5 1 4 ∴ 𝛼𝛼 = 2 − 2 = 2 = 2 5 5 𝛽𝛽 = 2 = 2 5 1 𝛾𝛾 = 2 + 2 = 3 4.Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ 5=5 𝛼𝛼𝛼𝛼𝛼𝛼 = −(−2) 2×1×1=2 2=2 2. Sol: Any cubic polynomial is of the form 𝑎𝑎𝑥𝑥 3 + 𝑏𝑏𝑥𝑥 2 + 𝑐𝑐𝑐𝑐 + 𝑑𝑑 = 𝑥𝑥 3 − 𝑠𝑠𝑠𝑠𝑠𝑠 𝑜𝑜𝑜𝑜 𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧 (𝑥𝑥 2 )[product of zeroes] + sum of the products of its zeroes × .com.

Sol: Let a – d. a + d be the zeroes of the polynomial f(x) −3𝑏𝑏 The sum of zeroes ⇒ a – d + a + a + d = 𝑎𝑎 3𝑏𝑏 −3𝑏𝑏 −𝑏𝑏 ⇒ +3a = − 𝑎𝑎 ⇒ 𝑎𝑎 = 𝑎𝑎×3 𝑎𝑎 = 𝑎𝑎 f(a) = 0 ⇒ a(a) + 3b(a) + 3 c(a) + d = 0 2 2 −𝑏𝑏 3 3𝑏𝑏 2 3𝑏𝑏𝑏𝑏 = a � 𝑎𝑎 � + − + 𝑑𝑑 = 0 𝑎𝑎2 𝑎𝑎 2𝑏𝑏 3 3𝑏𝑏𝑏𝑏 ⇒ − + 𝑑𝑑 = 0 𝑎𝑎2 𝑎𝑎 2𝑏𝑏 3 −3𝑎𝑎𝑎𝑎𝑎𝑎+𝑎𝑎2 𝑑𝑑 ⇒ 𝑎𝑎2 =0 ⇒ 2𝑏𝑏 − 3𝑎𝑎𝑎𝑎𝑎𝑎 + 𝑎𝑎2 𝑑𝑑 = 0 3 6.com. Sol: 𝑓𝑓(𝑥𝑥) = 𝑥𝑥 3 − 12𝑥𝑥 2 + 39𝑥𝑥 − 𝑘𝑘 Let 𝑎𝑎 − 𝑑𝑑.Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ 𝑏𝑏 𝑎𝑎 + 𝑎𝑎 − 𝑑𝑑 + 𝑎𝑎 + 𝑑𝑑 = 𝑎𝑎 3𝑎𝑎 = −3𝑝𝑝 a = −𝑝𝑝 Since a is the zero of the polynomial f(x) therefore f(a) = 0 ⇒ [𝑎𝑎]2 + 3𝑝𝑝𝑎𝑎2 + 3𝑞𝑞𝑞𝑞 + 𝑟𝑟 = 0 ∴ 𝑓𝑓(𝑎𝑎) = 0 ⇒ [𝑎𝑎]2 + 3𝑝𝑝𝑎𝑎2 + 3𝑞𝑞𝑞𝑞 + 𝑟𝑟 = 0 ⇒ 𝑝𝑝3 + 3𝑝𝑝(−𝑝𝑝)2 + 3𝑞𝑞(−𝑝𝑝) + 𝑟𝑟 = 0 ⇒ −𝑝𝑝3 + 3𝑝𝑝2 − 𝑝𝑝𝑝𝑝 + 𝑟𝑟 = 0 ⇒ 2𝑝𝑝3 − 𝑝𝑝𝑝𝑝 + 𝑟𝑟 = 0 5. 𝑎𝑎 + 𝑑𝑑 be the zeroes of the polynomial f(x) The sum of the zeroes = 12 3a = 12 a=4 𝑓𝑓(𝑎𝑎). −𝑎𝑎(𝑥𝑥)3 − 𝑙𝑙 2 (4)2 + 39(4) + 𝑘𝑘 = 0 64 – 192 + 156 + k = 0 = −28 = 𝑘𝑘 k = −28 Printed from Vedantu. Book a free session with a top LIVE online tutor now. 13 . a. 𝑎𝑎.

com.3 1. Book a free session with a top LIVE online tutor now. 14 . Sol: (i) 𝑓𝑓(𝑥𝑥) = 𝑥𝑥 3 − 6𝑥𝑥 2 + 11𝑥𝑥 − 6 g(x) = 𝑥𝑥 2 + 𝑥𝑥 + 1 𝑥𝑥 − 7 𝑥𝑥 + 𝑥𝑥 + 1 𝑥𝑥 3 − 6𝑥𝑥 2 + 11𝑥𝑥 − 6 2 𝑥𝑥 3 + 𝑥𝑥 2 + 𝑥𝑥 −7𝑥𝑥 2 − 7𝑥𝑥 − 7 −7𝑥𝑥 2 − 7𝑥𝑥 − 7 17𝑥𝑥 − 1 (ii) 𝑓𝑓(𝑥𝑥) = 10𝑥𝑥 + 17𝑥𝑥 3 − 62𝑥𝑥 2 + 30𝑥𝑥 − 105(𝑥𝑥) = 2𝑥𝑥 2 + 7𝑥𝑥 + 1 4 5𝑥𝑥 2 − 9𝑥𝑥 − 2 2𝑥𝑥 2 + 7𝑥𝑥 + 1 10𝑥𝑥 4 + 17𝑥𝑥 3 − 62𝑥𝑥 2 + 30𝑥𝑥 − 3 10𝑥𝑥 4 + 35𝑥𝑥 3 + 5𝑥𝑥 2 −18𝑥𝑥 3 − 67𝑥𝑥 2 + 30𝑥𝑥 −18𝑥𝑥 3 ± 63𝑥𝑥 2 + 9𝑥𝑥 −4𝑥𝑥 2 + 39𝑥𝑥 − 3 ±4𝑥𝑥 2 ± 14𝑥𝑥 ± 2 53𝑥𝑥 − 1 (iii) 𝑓𝑓(𝑥𝑥) = 4𝑥𝑥 + 8𝑥𝑥 + 8𝑥𝑥 + 7: 9(𝑥𝑥) = 2𝑥𝑥 2 − 𝑥𝑥 + 1 3 2 2x – 5 2𝑥𝑥 − 2 + 1 4𝑥𝑥 + 8𝑥𝑥 2 + 82 + 7 2 3 4𝑥𝑥 3 ∓ 2𝑥𝑥 2 ± 2𝑥𝑥 10𝑥𝑥 2 + 6𝑥𝑥 + 7 10𝑥𝑥 2 ± 5𝑥𝑥 ± 5 11x – 2 (iv) 𝑓𝑓(𝑥𝑥) = 15𝑥𝑥 − 20𝑥𝑥 + 13𝑥𝑥 − 12. 𝑔𝑔(𝑥𝑥) = 𝑥𝑥 2 − 2𝑥𝑥 + 2 3 2 15𝑥𝑥 + 10 𝑥𝑥 − 2𝑥𝑥 + 2 15𝑥𝑥 − 20𝑥𝑥 2 + 13𝑥𝑥 − 12 2 3 15𝑥𝑥 3 ∓ 30𝑥𝑥 2 ± 30𝑥𝑥 10𝑥𝑥 2 − 17𝑥𝑥 − 12 10𝑥𝑥 2 ± 20𝑥𝑥 + 20 3x – 32 Printed from Vedantu.Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ Exercise 2.

𝑓𝑓(𝑡𝑡) = 2𝑡𝑡 4 + 3𝑡𝑡 3 − 2𝑡𝑡 2 − 9𝑡𝑡 2𝑡𝑡 2 + 3𝑡𝑡 + 4 𝑡𝑡 2 − 3 2𝑡𝑡 4 + 3𝑡𝑡 3 − 2𝑡𝑡 2 − 9𝑡𝑡 2𝑡𝑡 2 − 6𝑡𝑡 2 3𝑡𝑡 3 + 4𝑡𝑡 − 9𝑡𝑡 3𝑡𝑡 3 + 4𝑡𝑡 − 9𝑡𝑡 4𝑡𝑡 2 − 12 4𝑡𝑡 2 ∓ 12 (ii) 𝑔𝑔(𝑥𝑥) = 𝑥𝑥 2 − 3𝑥𝑥 + 1. Book a free session with a top LIVE online tutor now.Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ 2. then its factors are (x + 2) and (x + 1) (𝑥𝑥 + 2)(𝑥𝑥 + 1) = 𝑥𝑥 2 + 𝑥𝑥 + 2𝑥𝑥 = 𝑥𝑥 2 + 3𝑥𝑥 + 2 2𝑥𝑥 2 − 5𝑥𝑥 − 3 𝑥𝑥 2 + 3𝑥𝑥 + 2 2𝑥𝑥 4 + 𝑥𝑥 3 − 14𝑥𝑥 2 − 19𝑥𝑥 − 6 2𝑥𝑥 4 + 6𝑥𝑥 3 + 4𝑥𝑥 2 −5𝑥𝑥 3 − 18𝑥𝑥 2 − 19𝑥𝑥 −5𝑥𝑥 3 ∓ 15𝑥𝑥 2 ∓ 10𝑥𝑥 Printed from Vedantu. 𝑓𝑓(𝑥𝑥) = 𝑥𝑥 5 − 4𝑥𝑥 3 + 𝑥𝑥 2 + 3𝑥𝑥 + 1 𝑥𝑥 2 − 1 𝑥𝑥 3 − 3𝑥𝑥 + 1 𝑥𝑥 5 − 4𝑥𝑥 3 + 𝑥𝑥 2 + 3𝑥𝑥 + 1 𝑥𝑥 5 − 3𝑥𝑥 3 + 𝑥𝑥 2 −𝑥𝑥 3 + 3𝑥𝑥 + 1 −𝑥𝑥 3 + 3𝑥𝑥 − 1 2 (iii) 𝑔𝑔(𝑥𝑥) = 2𝑥𝑥 − 𝑥𝑥 + 3. Sol: 𝑓𝑓(𝑥𝑥) = 2𝑥𝑥 4 + 𝑥𝑥 3 − 14𝑥𝑥 2 − 19𝑥𝑥 − 6 If the two zeroes of the polynomial are -2 and -1. 𝑓𝑓(𝑥𝑥) = 6𝑥𝑥 − 𝑥𝑥 4 + 4𝑥𝑥 3 − 5𝑥𝑥 2 − 𝑥𝑥 − 15 2 5 3𝑥𝑥 3 + 𝑥𝑥 2 − 2𝑥𝑥 − 5 2𝑥𝑥 2 − 𝑥𝑥 + 3 6𝑥𝑥 5 − 𝑥𝑥 4 + 4𝑥𝑥 3 − 5𝑥𝑥 2 − 𝑥𝑥 − 15 6𝑥𝑥 5 − 3𝑥𝑥 4 + 9𝑥𝑥 3 2𝑥𝑥 4 − 5𝑥𝑥 3 − 5𝑥𝑥 2 2𝑥𝑥 4 ∓ 𝑥𝑥 3 ± 3𝑥𝑥 2 −4𝑥𝑥 3 − 8𝑥𝑥 2 − 𝑥𝑥 ∓4𝑥𝑥 3 ± 2𝑥𝑥 2 − 6𝑥𝑥 −10𝑥𝑥 2 − 5𝑥𝑥 − 15 ∓10𝑥𝑥 ± 15𝑥𝑥 ∓ 15 0 3. 15 . Sol: (i) 𝑔𝑔(𝑡𝑡) = 𝑡𝑡 2 − 3.com.

Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ −3𝑥𝑥 2 − 9𝑥𝑥 − 6 −3𝑥𝑥 2 − 9𝑥𝑥 − 6 ∴ 2𝑥𝑥 4 + 𝑥𝑥 3 − 14𝑥𝑥 2 − 19𝑥𝑥 − 6 = (2𝑥𝑥 2 − 5𝑥𝑥 − 3)[𝑥𝑥 2 + 3𝑥𝑥 + 2] = [2𝑥𝑥 + 1][𝑥𝑥 − 3][𝑥𝑥 + 2][𝑥𝑥 + 1] −1 ∴ zero all x = 2 . -2. Sol: 𝑓𝑓(𝑥𝑥) = (𝑥𝑥 2 − 3𝑥𝑥 + 2) = �𝑥𝑥 + √3�& �𝑥𝑥 − √3� = 𝑥𝑥 2 − 3 𝑥𝑥 2 − 3𝑥𝑥 + 2 𝑥𝑥 2 − 3 𝑥𝑥 4 − 3𝑥𝑥 2 = 𝑥𝑥 2 + 9𝑥𝑥 − 6 𝑥𝑥 4 − 3𝑥𝑥 2 −3𝑥𝑥 2 + 2𝑥𝑥 2 + 9𝑥𝑥 −3𝑥𝑥 2 ± 9𝑥𝑥 2 2𝑥𝑥 − 6 2𝑥𝑥 2 − 6 (𝑥𝑥 2 − 3)(𝑥𝑥 2 − 3𝑥𝑥 + 2) = �𝑥𝑥 + √3��𝑥𝑥 − √3�(𝑥𝑥 2 − 2𝑥𝑥 − 𝑥𝑥 + 2) = �𝑥𝑥 + √3��𝑥𝑥 − √3� (𝑥𝑥 − 2)(𝑥𝑥 − 2) Zeroes are −√3. −1 4. −2. 16 . 3.com. 2 Printed from Vedantu. √3. Sol: 𝑓𝑓(𝑥𝑥) = 𝑥𝑥 3 + 13𝑥𝑥 2 + 32𝑥𝑥 + 20 𝑥𝑥 2 + 11𝑥𝑥 + 10 𝑥𝑥 + 2 𝑥𝑥 3 + 13𝑥𝑥 2 + 32𝑥𝑥 + 20 𝑥𝑥 3 ± 2𝑥𝑥 2 11𝑥𝑥 2 + 32𝑥𝑥 + 20 11𝑥𝑥 2 ± 22𝑥𝑥 10x + 20 10x + 20 0 2 2 (𝑥𝑥 + 11𝑥𝑥 + 10) = 𝑥𝑥 + 10𝑥𝑥 + 𝑥𝑥 + 20(𝑥𝑥 + 10) + 1(𝑥𝑥 + 10) = (𝑥𝑥 + 1)(𝑥𝑥 + 10) ∴ The zeroes of the polynomial are -1. Book a free session with a top LIVE online tutor now. 1. -10. 5.

�2 − �2 7. 17 . Sol: 𝑥𝑥 2 − 1 𝑥𝑥 2 + 2𝑥𝑥 − 3 𝑥𝑥 4 + 2𝑥𝑥 3 − 2𝑥𝑥 2 + 𝑥𝑥 − 1 𝑥𝑥 4 + 2𝑥𝑥 3 − 3𝑥𝑥 2 𝑥𝑥 2 + 𝑥𝑥 − 1 𝑥𝑥 2 + 2𝑥𝑥 − 3 −x + 2 we must add x −2 in order to get the resulting polynomial exactly divisible by 𝑥𝑥 2 + 2𝑥𝑥 − 3 8.Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ 6. Book a free session with a top LIVE online tutor now. �2 . Sol: 𝑥𝑥 2 + 6𝑥𝑥 + 8 𝑥𝑥 2 − 4𝑥𝑥 + 3 𝑥𝑥 4 + 2𝑥𝑥 3 − 13𝑥𝑥 2 − 12𝑥𝑥 + 21 𝑥𝑥 4 − 4𝑥𝑥 3 + 3𝑥𝑥 2 6𝑥𝑥 3 − 16𝑥𝑥 2 − 12𝑥𝑥 6𝑥𝑥 3 − 24𝑥𝑥 2 − 18𝑥𝑥 8𝑥𝑥 2 − 30𝑥𝑥 + 21 Printed from Vedantu. Sol: 3 3 If the zeroes of the polynomial are −�2 𝑎𝑎𝑎𝑎𝑎𝑎 �2 √3 3 𝑥𝑥 2 −3 Its factors are �𝑥𝑥 + � �𝑥𝑥 − �2� = 2 2 3 3 x = −1. 2.com. 2. −�2 3 = [2𝑥𝑥 2 − 2𝑥𝑥 − 4] �𝑥𝑥 2 − 2� 3 = (2𝑥𝑥 2 − 4𝑥𝑥 + 2𝑥𝑥 − 4) �𝑥𝑥 + �2� = �2[𝑥𝑥(𝑥𝑥 + 2) + 2(𝑥𝑥 − 2)]� √3 3 = �𝑥𝑥 + � �𝑥𝑥 − �2� 2 3 3 = (𝑥𝑥 + 2)(𝑥𝑥 − 2) �𝑥𝑥 + �2� �𝑥𝑥 − �2� 3 3 𝑥𝑥 = −1.

Book a free session with a top LIVE online tutor now.com. 5] 10. (𝑥𝑥 − 2)(𝑥𝑥 + 2)𝑖𝑖𝑖𝑖 𝑎𝑎 𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓 𝑜𝑜𝑜𝑜 𝑓𝑓(𝑥𝑥) 𝑥𝑥 2 − 4 𝑖𝑖𝑖𝑖 𝑎𝑎 𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓 𝑥𝑥 2 + 𝑥𝑥 − 30 𝑥𝑥 2 − 4 𝑥𝑥 4 + 𝑥𝑥 3 − 34𝑥𝑥 2 − 4𝑥𝑥 + 120 −𝑥𝑥 4 − 4𝑥𝑥 2 𝑥𝑥 3 − 30𝑥𝑥 2 − 4𝑥𝑥 + 120 𝑥𝑥 3 − 4𝑥𝑥 2 −30𝑥𝑥 + 120 −30x 2 + 120 0 Hence. 18 . Sol: ⇒ 𝑓𝑓(𝑥𝑥) = 𝑥𝑥 4 + 𝑥𝑥 3 − 34𝑥𝑥 2 − 4𝑥𝑥 + 120 ⇒ x = −2 is a solution x = −2 is a factor x = −2 is a solution x = +2 is a factor here.Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ 8𝑥𝑥 2 − 32𝑥𝑥 + 21 2x – 2 We must subtract [2𝑥𝑥 − 2] + 10𝑚𝑚 the given polynomial so as to get the resulting polynomial exactly divisible by 𝑥𝑥 2 − 𝑥𝑥 + 3 9. −6. 𝑥𝑥 + 𝑥𝑥 − 34𝑥𝑥 − 4𝑥𝑥 + 120 = (𝑥𝑥 2 − 4)(𝑥𝑥 2 + 𝑥𝑥 − 30) 4 3 2 𝑥𝑥 4 + 𝑥𝑥 3 − 34𝑥𝑥 2 − 4𝑥𝑥 + 120 = (𝑥𝑥 2 − 4)(𝑥𝑥 2 + 6𝑥𝑥 − 5𝑥𝑥 − 30) 𝑥𝑥 4 + 𝑥𝑥 3 − 34𝑥𝑥 2 − 4𝑥𝑥 + 120 = (𝑥𝑥 2 − 4)��𝑥𝑥(𝑥𝑥 + 6) − 5(𝑥𝑥 + 6)�� 𝑥𝑥 4 + 𝑥𝑥 3 − 34𝑥𝑥 2 − 4𝑥𝑥 + 120 = (𝑥𝑥 2 − 4)(𝑥𝑥 + 6)(𝑥𝑥 − 5) Other zeroes are x+6=0 ⇒x–5=0 x=−6 x=5 Set of zeroes for f(x) [2. Sol: 𝑓𝑓(𝑥𝑥) = 2𝑥𝑥 4 + 7𝑥𝑥 3 − 19𝑥𝑥 2 − 14𝑥𝑥 + 30 𝑥𝑥 = √2 𝑖𝑖𝑖𝑖 𝑎𝑎 𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠 𝑥𝑥 − √2 𝑖𝑖𝑖𝑖 𝑎𝑎 𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠 𝑥𝑥 − √2 𝑖𝑖𝑖𝑖 𝑎𝑎 𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠 𝑥𝑥 + √2 𝑖𝑖𝑖𝑖 𝑎𝑎 𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓 Printed from Vedantu. −2.

−√2� 11. √2. 2 . Book a free session with a top LIVE online tutor now. 2𝑥𝑥 + 𝑥𝑥 − 6𝑥𝑥 − 3 = (𝑥𝑥 2 − 3)(2𝑥𝑥 + 1) 3 2 Other zeroes of f(x) is 2 × +1 = 0 1 𝑥𝑥 = − 2 Printed from Vedantu.Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ Here. �𝑥𝑥 + √2��𝑥𝑥 − √2�𝑖𝑖𝑖𝑖 𝑎𝑎 𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓 𝑜𝑜𝑜𝑜 𝑓𝑓(𝑥𝑥) 𝑥𝑥 2 − 2 𝑖𝑖𝑖𝑖 𝑎𝑎 𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓 𝑜𝑜𝑜𝑜 𝑓𝑓(𝑥𝑥) 2𝑥𝑥 2 + 7𝑥𝑥 − 15 𝑥𝑥 2 − 2 2𝑥𝑥 4 + 7𝑥𝑥 3 − 192 − 14𝑥𝑥 + 30 2𝑥𝑥 4 − 4𝑥𝑥 2 7𝑥𝑥 3 − 15𝑥𝑥 2 − 14𝑥𝑥 7𝑥𝑥 3 − −14𝑥𝑥 2 −15𝑥𝑥 + 30 2 −15𝑥𝑥 + 30 0 Hence. Sol: 𝑓𝑓(𝑥𝑥) = 2𝑥𝑥 3 + 𝑥𝑥 2 − 6𝑥𝑥 − 3 x = −√3 is a solution 𝑥𝑥 + √3 𝑖𝑖𝑖𝑖 𝑎𝑎 𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓 𝑥𝑥 = √3 𝑖𝑖𝑖𝑖 𝑎𝑎 𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠𝑠 𝑥𝑥 − √3 𝑖𝑖𝑖𝑖 𝑎𝑎 𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓 Here. 19 . �𝑥𝑥 + √3��𝑥𝑥 − √3�𝑖𝑖𝑖𝑖 𝑎𝑎 𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓 𝑜𝑜𝑜𝑜 𝑓𝑓(𝑥𝑥) 𝑥𝑥 2 − 3 𝑖𝑖𝑖𝑖 𝑎𝑎 𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓 𝑜𝑜𝑜𝑜 𝑓𝑓(𝑥𝑥) 2x + 1 𝑥𝑥 − 3 2𝑥𝑥 3 + 𝑥𝑥 2 − 6𝑥𝑥 − 3 2 2𝑥𝑥 3 − 6𝑥𝑥 2 𝑥𝑥 −3 2 𝑥𝑥 −3 0 Hence. 2𝑥𝑥 + 7𝑥𝑥 − 19𝑥𝑥 − 14𝑥𝑥 + 30 = (𝑥𝑥 − 2)(2𝑥𝑥 2 + 7𝑥𝑥 − 15) 4 3 2 2 = (𝑥𝑥 2 − 2) (2𝑥𝑥 2 + 10𝑥𝑥 − 3𝑥𝑥 − 15) = (𝑥𝑥 2 − 2)�2𝑥𝑥(𝑥𝑥 + 5) − 3(𝑥𝑥 + 5)� = (𝑥𝑥 2 − 2)(𝑥𝑥 + 5)(𝑥𝑥 − 3) Other zeroes are: x+5=0 2x – 3 = 0 x = −5 2x = 3 3 x=2 3 Hence the set of zeroes for 𝑓𝑓(𝑥𝑥) �−5.com.

20 .Class X Chapter 2 – Polynomials Maths ______________________________________________________________________________ −1 𝑆𝑆𝑆𝑆𝑆𝑆 𝑜𝑜𝑜𝑜 𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧 �√3. we have ⇒ 𝑥𝑥 3 + 3𝑥𝑥 2 − 2 − 6 = (𝑥𝑥 2 − 2)(𝑥𝑥 + 3) ⇒ 𝑥𝑥 3 + 3𝑥𝑥 2 − 2𝑥𝑥 − 6 = �𝑥𝑥 + √2��𝑥𝑥 − √2�(𝑥𝑥 + 3) Here the zeroes of the given polynomials are −√2. Book a free session with a top LIVE online tutor now. Sol: Since −√2 𝑎𝑎𝑎𝑎𝑎𝑎 √2 are zeroes of polynomial 𝑓𝑓(𝑥𝑥) = 𝑥𝑥 3 + 3𝑥𝑥 2 − 2𝑥𝑥 − 6 �𝑥𝑥 + √2��𝑥𝑥 − √2� = 𝑥𝑥 2 − 2 𝑖𝑖𝑖𝑖 𝑎𝑎 𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓 𝑜𝑜𝑜𝑜 𝑓𝑓(𝑥𝑥) Now we divide 𝑓𝑓(𝑥𝑥) = 𝑥𝑥 3 + 3𝑥𝑥 2 − 2𝑥𝑥 − 6 by 𝑔𝑔(𝑥𝑥) = 𝑥𝑥 2 − 2 𝑡𝑡𝑡𝑡 𝑏𝑏 𝑓𝑓𝑓𝑓𝑓𝑓𝑓𝑓 𝑡𝑡ℎ𝑒𝑒 𝑜𝑜𝑜𝑜ℎ𝑒𝑒𝑒𝑒 𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧𝑧 𝑜𝑜𝑜𝑜 𝑓𝑓(𝑥𝑥) 𝑥𝑥 + 3 𝑥𝑥 − 2 𝑥𝑥 3 + 3𝑥𝑥 2 − 2𝑥𝑥 − 6 2 𝑥𝑥 3 − 2𝑥𝑥 2 3𝑥𝑥 −6 2 3𝑥𝑥 −6 0 By division algorithm. −√3.com. √2 𝑎𝑎𝑎𝑎𝑎𝑎 − 3 Printed from Vedantu. 2 � 12.